A 22‐channel receive array with Helmholtz transmit coil for anesthetized macaque MRI at 3 T. (23rd May 2013) - Janssens, Thomas; Keil, Boris; Serano, Peter; Mareyam, Azma; McNab, Jennifer A.; Wald, Lawrence L.; Vanduffel, Wim
Abstract : The macaque monkey is an important model for cognitive and sensory neuroscience that has been used extensively in behavioral, electrophysiological, molecular and, more recently, neuroimaging studies. However, macaque MRI has unique technical differences relative to human MRI, such as the geometry of highly parallel receive arrays, which must be addressed to optimize imaging performance. A 22‐channel receive coil array was constructed specifically for rapid high‐resolution anesthetized macaque monkey MRI at 3 T. A local Helmholtz transmit coil was used for excitation. Signal‐to‐noise ratios (SNRs) and noise amplification for parallel imaging were compared with those of single‐ and four‐channel receive coils routinely used for macaque MRI. The 22‐channel coil yielded significant improvements in SNR throughout the brain. Using this coil, the SNR in peripheral brain was 2.4 and 1.7 times greater than that obtained with single‐ or four‐channel coils, respectively. In the central brain, the SNR gain was 1.5 times that of both the single‐ and four‐channel coils. Finally, the performance of the array for functional, anatomical and diffusion‐weighted imaging was evaluated. For all three modalities, the use of the 22‐channel array allowed for high‐resolution and accelerated image acquisition. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : A 22‐channel receive coil array with a local Helmholtz transmit coil was constructed for rapid high‐resolution anesthetized macaque monkey MRI at 3 T. Using this coil, the signal‐to‐noise ratio (SNR) in peripheral brain was 2.4 and 1.7 times greater than that obtained with single‐ and four‐channel coils, respectively. The improved SNR was exploited to acquire high‐resolution accelerated images with reduced required scan time for functional, anatomical and diffusion‐weighted imaging.